DAMPAK PULUNG GANTUNG (PENCIPTAAN DENGAN METODE SENI GRAFIS) - Kukuh Hernandi (Journal of Contemporary Indonesian Art, 2019)
Pulung Gantung is one of the mythology in Kabupaten Gunungkidul which the community at there still believing as it is supported by some logic reasons until now. In the myth, Pulung Gantung always illustrated as a fire ball which dropped from the sky as a symbol of the happening of self-hanging. This story related with the reality where the statistic of self-hanging in Kabupaten Gunungkidul happened to be around 28 to 32 cases per year. This case became interesting where myth could be connected to the reality directly and it is still believed by many (in where this case also experienced different development of variety definition), which indirectly created variety layers of impact. The complexity of this theme and different perspectives to define attracted the artist to carry out research and apply the outcome with the method of printmaking as a way to process the impact of Pulung Gantung. With the method of printmaking, it progressively attracted to the definition of printmaking slowly returned to the early essence of printmaking itself as a media without limitation of conventional rules. This strongly supported the artist to apply this media on this topic to have an open discussion about the impact of Pulung Gantung with the presentation of different medium like sound, words or product. The artist creates the work in different medium, hopefully could become a vague stimulant for a better understanding about the myth and the reality of this topic. Nevertheless, other than understanding, there is potential for audience to have new idea or other’s perspective about this topic as the work presented in an indirectly way. In this case, the outcome of the work about the impact of Pulung Gantung creates the possibilities of different conclusion and new perspectives. With this idea, the possibility from the impact of mythology intersects with the reality which unconsciously continue to be happened.